086 The rapid efficacy of natalizumab vs fingolimod in patients with active relapsing-remitting multiple sclerosis (RRMS): results from reveal, a randomised, head-to-head study. Issue 6 (24th May 2018) - Butzkueven, Helmut; Jeffery, Douglas; Arnold, Douglas L; Filippi, Massimo; Geurts, Jeroen JG; Dong, Qunming; Campbell, Nolan; Licata, Stephanie; Ho, Pei-Ran
Abstract : Introduction: REVEAL was designed as a 1 year, multicentre, randomised, rater- and sponsor-blinded, prospective study comparing natalizumab and fingolimod in patients with active RRMS. Although the study closed early (for non-safety/non-efficacy reasons), data permitted comparison of effects occurring shortly after treatment initiation. This analysis compares onset of efficacy with natalizumab and fingolimod in REVEAL. Methods: Patients were randomised to open-label intravenous natalizumab 300 mg every 4 weeks (n=54) or oral fingolimod 0.5 mg once daily (n=54). Magnetic resonance imaging was scheduled every 4 weeks for the first 24 weeks and at weeks 36 and 52. Analyses included Kaplan-Meier and Cox regression, negative binomial regression (annualised relapse rate [ARR] and number of T1 gadolinium-enhancing [Gd+] lesions) and a negative binomial generalised estimating equation (cumulative Gd +lesions over time). Results: As expected for a randomised study, patient characteristics and follow-up time (median 39 weeks) were generally similar between groups. Natalizumab patients were less likely than fingolimod patients to develop new Gd +lesions (for ≥1 lesion, cumulative probability 40.68% vs 57.99%; hazard ratio [HR]=1.678 [95% CI: 0.865 to 3.255]; p=0.1258; for ≥2 lesions, cumulative probability 11.54% vs 48.48%; HR=4.053 [95% CI: 1.474 to 11.144]; p=0.007). Natalizumab patients consistently had 63%–72% fewer Gd +lesions than fingolimod patients, with between-group differences apparent within 4 weeks and reaching significance by 12 weeks (p=0.030). ARR was 83% lower with natalizumab than with fingolimod (0.05 vs 0.29; p=0.023), and cumulative probability of relapse was 1.85% with natalizumab vs 22.28% with fingolimod (HR=12.184 [95% CI: 1.552 to 95.634]; p=0.017). Adverse events were consistent with known safety profiles. Conclusion: These results suggest that natalizumab reduces disease activity more rapidly and to a greater extent than fingolimod in patients with active RRMS. Given the early study closure, available data did not permit primary endpoint evaluation, and interpretation of these results requires caution. Study Support: Biogen.